Development Media Learning Audio Visual Based on Web Blog for Increasing Economy Learning Result - Alfis Aldera; Arwansyah Arwansyah; Fitrawaty Fitrawaty (Randwick International of Education and Linguistics Science Journal, 2024)
Media is one component that is really needed in learning. Teachers as facilitators in learning are required to be able to provide learning media that is suitable for use in learning. However, based on the results of field observations, it was found that there was still a lack of use of learning media in the learning process. The aim of this research is to develop and implement Web Blog-based audio- visual economics learning media to improve learning outcomes in the Taxation economics subject for class XI IPS students at SMA Negeri 1 Takengon. This research is development research (R&D) using the Four-D (4D) method. This research was conducted at SMA Negeri 1 Takengon, with a population of class XI IPS. The results of this research are based on assessments carried out by validation experts and user responses, an average assessment percentage of 93.70% was obtained in the "very feasible" category, so it was concluded that the Web Blog-based audio-visual learning media developed met the eligibility requirements (valid) to be used as a economics learning media for class XI IPS. The average learning outcome for the experimental class was 85.00 and for the control class 75.00, the results of the independent T-Test were 6.087>1.643 with sig. 0.00 < 0.05 and media can help students understand the material presented. So, it can be concluded that the Web Blog-based audio-visual economic learning media developed is effectively used to help students improve economic learning outcomes for class XI IPS SMA Negeri 1 Takengon.